Digital Storytelling, an ICT-based method of Coconstructing and Transacting Curriculum - Ranganathan, Sriranjani; Kasinathan, Gurumurthy (Voices of Teachers and Teacher Educators, 2017)
The present paper is the documentation of the ‘Digital Storytelling’ (DST) project run by the authors with teachers and students in seven different goverment high schools. This academic process of creating digital stories and using them in several educational endevours are the central theme of this paper.